Alanine Enhances Aminoglycosides-Induced ROS Production as Revealed by Proteomic Analysis - Ye, Jin-zhou; Su, Yu-bin; Lin, Xiang-min; Lai, Shi-shi; Li, Wan-xin; Ali, Farman; Zheng, Jun; Peng, Bo (Frontiers in Microbiology, 2018)
Metabolite-enabled killing of antibiotic-resistant pathogens by antibiotics is an attractive strategy to manage antibiotic resistance. Our previous study demonstrated that alanine or/and glucose increased the killing efficacy of kanamycin on antibiotic-resistant bacteria, whose action is through up-regulating TCA cycle, increasing proton motive force and enhancing antibiotic uptake. Despite several metabolic pathways promoted by alanine were demonstrated, other mechanisms potentially involved in the process remains to be explored. In the present study, we adopted proteomic approach to analyze the proteome changes induced by exogenous alanine. Our results revealed that the expression of three outer membrane proteins was altered, which the deletion of nagE and fadL decreased intracellular concentration implying their possible roles in mediating kanamycin transport. More importantly, the integrated analysis of proteomic and metabolomics data pointed out that alanine metabolism could connect to riboflavin metabolism that provides the source for reactive oxygen species (ROS) production. Functional studies confirmed alanine treatment together with kanamycin could promote ROS production that in turn potentiates the killing of antibiotic-resistant bacteria. Further investigation showed that alanine repressed the transcription of antioxidants, and alanine metabolism to riboflavin metabolism connected with riboflavin metabolism through TCA cycle, glucogenesis pathway and pentose phosphate pathway. Our results suggest a novel mechanism by which alanine facilitates kanamycin killing of antibiotic-resistant bacteria via promoting ROS production.